Giant Spinal Schwannomas: Report of Two Rare Cases with Interdisciplinary Surgical Resection - Carlos Erosa Velázquez; Sergio Ivan Reyna Heredia; Apolinar de la Luz Lagunas; Ramiro Lopez Elizalde; Cuauhtémoc Gil-Ortiz Mejia; Erika Paola Uc Montero; Edwin Rolando Sanchez Vallejo; Alejandra Grisel Mendoza Zúñiga; Gilfredo Jose Gonzalez Basile; Andres Jaime Aguirre (New Advances in Medicine and Medical Science Vol. 6, 2023)
This chapter reports two quite rare cases of giant schwannomas of the cervical and thoracic spine. Schwannomas are tumors that develop from Schwann cells in the neural sheath. Usually, these neoplasms are treated with surgical resection. The first patient is a 48-year-old man who presented to our clinic with complaints of weakness and paresthesia in both his lower and upper left extremities, as well as a sizable dorsal palpable mass. The diagnosis of the huge cervical schwannoma was made using MRI and CT scan. He had surgery because the severity of his problems required it. For both intravertebral and extravertebral techniques, multidisciplinary resection involving neurosurgery and oncosurgical teams was carried out. The second patient is a 55-year-old woman who complained of incapacitating pain and dysesthesia involving the T6, T7, and T8 dermatomes but had no additional impairments when she arrived at the hospital. Giant thoracic schwannoma was identified using an MRI and CT scan. Surgery was chosen as the preferred course of treatment due to the severity of the discomfort. Total resection was achieved via video assisted thoracoscopic surgery, and the symptoms have improved. Following surgery, both patients completely recovered from their symptoms and experienced no significant deficits. Although rare, visible lumps in the back with radicular symptoms may be caused by Giant spinal schwannomas. When they are asymptomatic, conservative treatment may be an option, but when they exhibit symptoms, surgery provides positive outcomes.